2015
DOI: 10.1080/03601234.2015.1028855
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sunn hemp (Crotalaria junceaL.) cutting date and planting density on weed suppression in Georgia, USA

Abstract: A field study was conducted in 2008 and 2009 at the USDA, ARS, Plant Genetic Resources Conservation Unit in Griffin, GA, to investigate weed suppression by sunn hemp (Crotalaria juncea L). The objectives were to (1) evaluate the effects of apical meristem removal (AMR) at three dates [5, 6, and 7 wks after planting (WAP) on May 14, 2008 and May 21, 2009] and (2) assess the impact of seeding rates (11, 28, and 45 kg ha(-1)) on weed biomass reduction. Weed species were identified at 4, 8, and 12 wks after sunn h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 19 publications
0
12
0
1
Order By: Relevance
“…This indicates that sunn hemp may have some ability to respond to low populations and maintain yield when provided adequate irrigation. Multiple studies have found that reduced seeding rates promote lateral branching in sunn hemp (Cho et al, 2015;Morris et al, 2015;Wang et al, 2009). Jaramillo et al (2020) found that seeding rates from 17 to 39 kg ha −1 did not result in differences in biomass yield at 50 DAP, which supports the idea that increased lateral branching may compensate for yield losses at reduced plant densities.…”
Section: Crop Sciencementioning
confidence: 73%
“…This indicates that sunn hemp may have some ability to respond to low populations and maintain yield when provided adequate irrigation. Multiple studies have found that reduced seeding rates promote lateral branching in sunn hemp (Cho et al, 2015;Morris et al, 2015;Wang et al, 2009). Jaramillo et al (2020) found that seeding rates from 17 to 39 kg ha −1 did not result in differences in biomass yield at 50 DAP, which supports the idea that increased lateral branching may compensate for yield losses at reduced plant densities.…”
Section: Crop Sciencementioning
confidence: 73%
“…Sunn hemp, Crotalaria juncea L., is a warm-season legume that is planted before or after a vegetable cash crop to add nutrients and organic matter to the soil (Cherr et al, 2006(Cherr et al, , 2007Mansoer et al, 1997;Wang et al, 2005). This cover crop provides other benefits to growers such as suppression of weeds (Adler and Chase, 2007;Cho et al, 2015;Collins et al, 2008;Javaid et al, 2015;Morris et al, 2015;Mosjidis and Wehtje, 2011) and suppression of plant-parasitic nematode populations by not providing resources (Bhan et al, 2010;Braz et al, 2016). Sunn hemp is available to growers in northern Florida, where 10,000 ha of vegetables (potatoes, Solanum tuberosum L., and cabbage, Brassica oleracea L. var.…”
mentioning
confidence: 99%
“…ese results concur with those of Adler and Chase [42] who reported the germination inhibition of smooth amaranth (Amaranthus hybridus L.), bell pepper (Capsicum annuum L.), and tomato (Solanum esculentum L.) where extracts and mulches of black sunnhemp were used. Black sunnhemp roots, leaves, stems, and seeds are known to contain several dehydropyrrolidizine alkaloids such as junceine, trichodesmine, isohemijunceines A, B, C, and acetyl isohenmijunceines [8]. Pilbeam and Bell [43] identified the nonprotein 5-hydroxy-2-aminohexanoic acid as the allelochemical responsible for the phytotoxic activity exhibited by black sunnhemp.…”
Section: Discussionmentioning
confidence: 99%
“…Weed suppression when cover crop residues are incorporated into the soil may occur via altered nutrient dynamics depending on several other factors including type of tillage used, carbon to nitrogen ratio (C : N) of the decomposing cover crop material, soil type, and the environment [5]. In addition, cover crops can suppress weeds by competing for resources [6], disruption of life cycles of crop bound and crop associated weeds [7], through resource and light competition [8,9], creation of soil conditions that promote seed decay and predation [10], and prevention of weed seed set and dispersal [5]. Furthermore, some cover crops such as stooling rye (Secale cereal L.), barley (Hordeum vulgare L.), and black sunnhemp (Crotalaria juncea L.) have demonstrated allelopathic activity [11][12][13].…”
Section: Introductionmentioning
confidence: 99%